The Effect of Professional Competence and Ethics on Auditor Performance (Case Study at The Serdang Bedagai Regency Inspectorate Office) - Yuli Anra Damanik; Ayu Kurnia Sari (International Journal of Society and Law, 2024)
"The Influence of Professional Competence and Ethics on Auditor Performance (Case Study at the Serdang Bedagai Regency Inspectorate Office)" is the title of this research project. The purpose of this study is to find out three things: (1) the influence of auditor competence on the performance of auditors working in the Serdang Bedagai Regency inspectorate; (2) the influence of auditor professional ethics on the performance of auditors working in Serdang Bedagai Regency; and (3) the influence of professional competence and ethics on the performance of auditors working in Serdang Bedagai Regency. The examination approach used in this exploration is a quantitative methodology. Respondents were then detailed using factual techniques, namely legitimacy test, dependency test, traditional assumption test, normality test, multicollinearity test, heteroscedasticity test, speculation test and guarantee coefficient test.